Karakterisasi dan Kelayakan Ekonomi Citrus aurantifolia kultivar ‘Nimas Agrihorti’ sebagai Komoditas Biofarmasi Potensial di Indonesia - Budiyati, Emi; Waluyo, Budi; Maghfoer, Moch. Dawam; Kosmiatin, Mia; Triwiratno, Anang; Hanif, Zainuri; Andrini , Anis; Hanim, Faridha; Tina , Siti Agus (Buitenzorg: Journal of Tropical Science, 2025)
‘Nimas Agrihorti’ is a citrus cultivar developed to fulfil the increasing domestic demand for biopharmaceutical-grade citrus in Indonesia. Its development aligns with the growing public interest in health-promoting agricultural products. This study aimed to evaluate the morphological characteristics, chemical composition, and economic viability of ‘Nimas Agrihorti’ as a biopharmaceutical citrus. Field observations were conducted from June 2019 to October 2020 at the Banjarsari Experimental Field, Bayeman Village, Probolinggo, East Java. Morphological assessments followed the Descriptor List for Citrus by IPGRI, and chemical analyses were performed at the Post-Harvest Laboratory of Brawijaya University, Malang. Economic feasibility was assessed by calculating production costs and revenues over a 2-year cultivation cycle. ‘Nimas Agrihorti’ exhibited favorable morphological traits, including large fruit size (72–82 g), yellow skin, and sweet taste. Chemical analysis revealed vitamin C content of 34.8 mg/100 g and low acidity at 0.45%. The total production cost over 2 years was IDR 42,640,000.00 (equivalent to USD 2,584), with total revenue amounting to IDR 77,360,000.00 (equivalent to USD 4,688), resulting in a Revenue-Cost (R/C) ratio of 2.81. The combination of desirable morphological and chemical characteristics, along with strong economic returns, indicates that ‘Nimas Agrihorti’ holds significant potential for development as a biopharmaceutical citrus cultivar in Indonesia.   Keywords: citrus, cultivar, biopharmaceutical products, economic feasibility